Learning to Filter Text in Forum Malay Message using Naive Bayesian Technique - Ab. Halim, Norhadila (Universiti Teknologi Petronas, 2006)
Applying the basic filtering technique in forum application has been discussed in [I]. The paper explains about me use of the basic naive Bayesian algorithm to classify forum messages whether clean or bad where clean message has no bad words, while bad message contains at least one bad word. In this Final Year Project paper, the application ofthe algorithm in the filtering forum messages will be discussed in the attempt to apply learning to filter forum messages.